Institutionalizing Instructional Supervision Praxis to Improve Reading Performance Among Grade 1 Learners - Ibrahim, Anhar; Pajiji, Jocelyn; Imuy, Analyn; Kalimuddin, Shernalyn; Aminulla, Judylyn; Lastam, Lena (International Journal of Sustainability and Advanced Integrated Research, 2026)
This action research examined the effectiveness of institutionalizing a developmentally responsive instructional supervision praxis in improving the reading performance of Grade 1 learners in a public elementary school context in Bongao, Tawi-Tawi. Anchored on instructional supervision theory and guided by the Plan–Act–Observe–Reflect (PAOR) cycle, the study employed a quali-quantitative design involving 27 learners who participated in a one-month supervision-supported reading intervention. Quantitative data were gathered using pre-test and post-test reading assessments, while qualitative data were obtained through observation logs, supervision checklists, coaching notes, and teacher reflective journals. Results revealed a significant improvement in reading performance, with independent readers increasing from 3 to 7 and non-readers decreasing from 10 to 2. Statistical analysis confirmed a significant difference (t(26) = 9.72, p < .001). Qualitative findings indicated enhanced learner engagement, improved instructional consistency among teachers, and strengthened reflective teaching practices. Challenges such as learner fatigue and limited parental support were also observed. The study concludes that institutionalizing instructional supervision praxis is an effective and sustainable approach to improving early grade literacy. It recommends the expansion of supervision-based reading programs, sustained coaching and feedback, targeted remediation, and replication in similar educational contexts. This study supports Sustainable Development Goal 4 (Quality Education) by promoting inclusive and equitable literacy development across diverse educational settings. It contributes to sustainability by strengthening institutional practices, enhancing teacher capacity, and fostering long-term improvements in learner outcomes in low-performing educational environments.
Keywords: Action Research, BARMM, Grade 1 Learners, Instructional Supervision, Reading Performance